SUNAN GESENG: THE CATALYST OF ISLAMIC RENAISSANCE IN 15TH CENTURY KEDIRI - Ningtiyas, Lintang Ayu; Ayundasari, Lutfiah (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2023)
ABSTRACTThe process of Islamization in Nusantara, especially in Java, cannot be separated from the role of Wali Songo. This role found momentum in the form of Islamic institutionalization through the Demak Sultanate, which was the first Islamic sultanate in Java. This sultanate could dominate almost all Java regions, including Kediri. Islam in Kediri was spread by Sunan Geseng, a student of Sunan Kalijaga who was given the task of spreading Islam to the southern part of Java. Researchers found that Sunan Geseng played a role in the spread of Islam in Kediri around the 15th century. In this research, researchers used historical methods with research stages, namely, heuristics, criticism, interpretation, and historiography. This research aims to determine Sunan Geseng's role in spreading Islam in Kediri around the 15th century. Researchers found that Sunan Geseng traveled around the 15th century to spread Islam, including Kediri, after the Demak sultanate's founding. In Kediri, he used the Bil-hikmah da'wah method in preaching, founded a hermitage to teach Islamic teachings, and gave advice related to Islam.Keywords: Islamization, Kediri, the Role of Sunan Geseng ABSTRAKProses Islamisasi di Nusantara khususnya di Jawa tidak terlepas dari peran Wali Songo. Peran ini menemukan momentum dalam bentuk institusionalisasi Islam melalui Kesultanan Demak yang merupakan kesultanan Islam pertama di Jawa. Kesultanan ini mampu menghegemoni nyaris seluruh wilayah di Jawa termasuk Kediri. Islam di Kediri salah satunya disebarkan oleh Sunan Geseng yang merupakan murid Sunan Kalijaga yang mendapatkan tugas untuk menyebarkan agama Islam ke Pulau Jawa bagian selatan. Peneliti menemukan bahwa Sunan Geseng berperan terhadap penyebaran agama Islam di Kediri sekitar abad ke-15. Dalam penelitian ini, peneliti menggunakan metode historis dengan tahapan penelitian yaitu, heuristik, kritik, interpretasi, dan historiografi. Penelitian ini bertujuan untuk mengetahui peranan Sunan Geseng dalam penyebaran agama Islam di Kediri sekitar abad ke-15. Dari penelitian tersebut, peneliti mendapatkan hasil bahwa Sunan Geseng sekitar abad ke 15 melakukan perjalanan menyebarkan agama Islam termasuk ke Kediri setelah berdirinya kesultanan Demak. Di Kediri, beliau menggunakan metode dakwah Bil-hikmah dalam berdakwah, mendirikan padepokan untuk mengajarkan ajaran-ajaran Islam, serta memberikan nasihat-nasihat yang berhubungan dengan keislaman.Kata kunci: Islamisasi, Kediri, Peranan Sunan Geseng